Modern Greek Church Fairs and Pilgrimage Tourism - Varvounis, Manolis; PhD, Nicos Rodosthenous (European Journal of Multidisciplinary Studies, 2017)
The systematic study of church fairs, especially those of urban parishes in large urban centers, as carried out in recent years, has shown that there are many new customary and ritual forms that are created and adopted, often transformed to be enriched and made more attractive to the people. ?n this notice we will deal with certain interesting aspects of this contemporary customary reality. Through this adoption of customary forms, with their subsequent changes and amendments by the people on the basic characteristics of its live tradition, both the renewal of the tradition and the enrichment of the customary life of the people is achieved. This, in turn, is essential for the vitality and the continuation of the social impact and the acceptance of the tradition, which is an active procedure in progress, and not a set of fossilized situations, things, opinions, and actions. This is directly connected to the interior pilgrimage tourism since the organized visits of the believers to a place are frequent, specifically in order to take part in some great religious festival, which takes place there. In this process, the so critical from a cultural perspective since it’s linked to the substance of our daily tradition itself, the novel elements of our contemporary religious fairs are critical points, as shown above in detail.